2015
DOI: 10.1186/s12879-015-1167-6
|View full text |Cite
|
Sign up to set email alerts
|

Review of economic evaluations of mask and respirator use for protection against respiratory infection transmission

Abstract: BackgroundThere has been increasing debate surrounding mask and respirator interventions to control respiratory infection transmission in both healthcare and community settings. As decision makers are considering the recommendations they should evaluate how to provide the most efficient protection strategies with minimum costs. The aim of this review is to identify and evaluate the existing economic evaluation literature in this area and to offer advice on how future evaluations on this topic should be conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 49 publications
(135 reference statements)
0
16
0
4
Order By: Relevance
“…Eight [2633] review the effectiveness of pandemic influenza vaccine in preventing influenza and influenza-like illness (ILI); three [3436] examine the impact of antivirals; two [32, 37] review the effectiveness of seasonal influenza vaccines in preventing pandemic influenza infection; two evaluate the impact of personal protective measures (hand-washing, mask use) [38, 39]; one [40] analyzes the impact of school closure; and another [41] reviews the efficacy of traditional Chinese medicine (TCM). One review [42] evaluates the economic viability of a wide range of pharmaceutical and non-pharmaceutical measures, concluding that social distancing, antiviral prophylaxis, school closure, and vaccination are likely to be cost-effective in all settings, while quarantine is never cost-effective.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight [2633] review the effectiveness of pandemic influenza vaccine in preventing influenza and influenza-like illness (ILI); three [3436] examine the impact of antivirals; two [32, 37] review the effectiveness of seasonal influenza vaccines in preventing pandemic influenza infection; two evaluate the impact of personal protective measures (hand-washing, mask use) [38, 39]; one [40] analyzes the impact of school closure; and another [41] reviews the efficacy of traditional Chinese medicine (TCM). One review [42] evaluates the economic viability of a wide range of pharmaceutical and non-pharmaceutical measures, concluding that social distancing, antiviral prophylaxis, school closure, and vaccination are likely to be cost-effective in all settings, while quarantine is never cost-effective.…”
Section: Resultsmentioning
confidence: 99%
“…Of the two systematic reviews analyzing personal protective measures an influenza epidemic, one [39] reported on its effectiveness in preventing infection, while the other [38] discussed its economic benefit. Wong et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is difficult to compare the results of our evaluation to these previous high income setting studies as they often did not report results in an easily comparable format (e.g. cost per case prevented) and most did not use clinical trial efficacy data to inform their analyses [33].…”
Section: Discussionmentioning
confidence: 99%
“…The determination of cost-effectiveness will depend on the willingness to pay to prevent a CRI case in a HCW and this varies between countries and is not easily transferrable between different settings. The extent to which a decision maker is likely to focus on cost-effectiveness evidence when it comes to HCW protection will in part depend on the seriousness of the infections being prevented [33,38]. In the case of a highly pathogenic pandemic, respirator use in HCWs would likely be a cost-effective intervention.…”
Section: Discussionmentioning
confidence: 99%